Bottom-up influences of voice continuity in focusing selective auditory attention - Bressler, Scott (Psychol Res, 2014)
Selective auditory attention causes a relative enhancement of the neural representation of important information and suppression of the neural representation of distracting sound, which enables a listener to analyze and interpret information of interest. Some studies suggest that in both vision and in audition, the “unit” on which attention operates is an object: an estimate of the information coming from a particular external source out in the world. In this view, which object ends up in the attentional foreground depends on the interplay of top-down, volitional attention and stimulus-driven, involuntary attention. Here, we test the idea that auditory attention is object based by exploring whether continuity of a non-spatial feature (talker identity, a feature that helps acoustic elements bind into one perceptual object) also influences selective attention performance. In Experiment 1, we show that perceptual continuity of target talker voice helps listeners report a sequence of spoken target digits embedded in competing reversed digits spoken by different talkers. In Experiment 2, we provide evidence that this benefit of voice continuity is obligatory and automatic, as if voice continuity biases listeners by making it easier to focus on a subsequent target digit when it is perceptually linked to what was already in the attentional foreground. Our results support the idea that feature continuity enhances streaming automatically, thereby influencing the dynamic processes that allow listeners to successfully attend to objects through time in the cacophony that assails our ears in many everyday settings.